ANALISIS KARAKTERISTIK INDIVIDU DAN PEKERJAAN TERHADAP KINERJA TENAGA KESEHATAN DALAM KELENGKAPAN REKAM MEDIS DI RUMAH SAKIT LARAS KABUPATEN SIMALUNGUN - Putri Sarah Zahrani (Jurnal Inovasi Kesehatan Masyarakat, 2023)
Medical records are activities that must be carried out by every health facility, especially hospitals as a guideline for health services to patients. Health workers in completing medical records should have knowledge of completing patient medical record files. Laras Hospital is a type C hospital managed by PTPN IV's subsidiary, PT Prima Medica Nusantara (PMN), all indicators of completeness of medical records at Laras Hospital in several years are still unable to meet service quality standards. This means that the performance target of health workers in the completeness of medical records has not been able to be achieved. The type of ths research is quantitative, and the approachof this research is cross sectional approach, ordinal scale type (likert), non-parapmetric statistical test type, data analysis method using univariate and bivariate analysis using the Spearman Rank test using SPSS Version 25 software. The results of the study stated that each indicator of individual characteristics (interests, attitudes and abilities) and indicators of job characteristics (skill variety, task identity, task significance, autonomy and feedback) were positively and significantly related to health workers in the completeness of medical records at Laras Hospital. The most dominant factor related to the performance of health workers in the completeness of medical records at Laras Hospital is the individual characteristic variable is interest, while the job characteristic variable is the significance of the task.